(untitled) (Revista de Ciências Agroveterinárias, 2022)
Physalis peruviana (Solanaceae) is an exotic fruit that is still little cultivated in Brazil when compared to other species. As a result, information related to management that can contribute to the development of the crop and pest control is scarce. Thus, the objective of this work was to evaluate the effects of spraying diatomaceous earth (DE) on the phytotechnical parameters of the crop and fruit quality, as well as on the induced resistance to arthropods pest in P. peruviana. The experimental design was in randomized blocks, with five treatments, which refer to the concentrations of DE (T1 - 0 g L-1; T2 - 1 g L-1; T3 - 3 g L-1; T4 - 6 g L-1 and T5 - 9 g L-1) and eight blocks. Phytotechnical characteristics of the crop and quality (soluble solids) of the fruits were evaluated, as well as the induction of resistance by evaluating the incidence of arthropods pest. There was no significant difference between the DE concentrations for the phytotechnical and quality variables and those related to the feeding preference of herbivorous insects (number and percentage of leaves with holes). However, plants treated with DE were less preferred for oviposition by Bemisia tabaci and Lema bilineata, and fewer whitefly adults and L. bilineata larvae and adults were also recorded. Thus, it is concluded that DE has no effect on phytotechnical and quality parameters of physalis, but induces resistance against arthropods pest such as B. tabaci and L. bilineata.